Use of Smartphones in Hospitals. Issue 4 (October 2015) - Unknown
Abstract : Mobile technology has begun to change the landscape of the medical profession, with more than two-thirds of physicians regularly using smartphones. Smartphones have allowed health care professionals and the general public to communicate more efficiently, collect data, and facilitate clinical decision making. The methodology for this study was a qualitative literature review following a systematic approach of smartphone use among physicians in hospitals. Fifty-one articles were selected for this study based on inclusion criteria. The findings were classified and described into 7 categories: use of smartphone in obstetrics, pediatrics, surgery, internal medicine, radiology, and dermatology, which were chosen based on the documented use of smartphone application in different health care practices. A last section of patient safety and issues with confidentiality is also described. This study suggests that smartphones have been playing an increasingly important role in health care. Medical professionals have become more dependent upon medical smartphone applications. However, concerns of patient safety and confidentiality will likely lead to increased oversight of mobile device use by regulatory agencies and accrediting bodies.